El desarrollo de los actos del habla a través de la interacción del trabajo grupal entre los estudiantes de noveno año c en la unidad educativa Dr. Manuel Agustín cabrera lozano de la ciudad de Loja durante el año escolar 2016-2017 - Robalino Sanchez, Denise Estefania (2018)
The following research work was carried out to develop speech acts through group work interaction among students of ninth year C of the Dr. Manuel Agustín Cabrera Lozano high school. The scientific, descriptive, analytic-synthetic and statistical methods were used to analyzed the information gathered. Tests and questionnaires were applied to the twenty-seven students before and after of the intervention plan. The information obtained was presented in tables and figures. The main result of the present research work showed that students understood and used better some speech acts to communicate properly in the English language. These acts are apologies, greetings, commands, requests and idioms. It is concluded that the application of the of group work interaction was excellent, since, students at the end of the intervention plan developed and increased significantly the participation, communication, relationship, and cooperation in the English classes.